2020
DOI: 10.3934/publichealth.2020052
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of COVID-19 related stress, anxiety and depression associated with intense mass media coverage in Saudi Arabi

Abstract: The Coronavirus Disease 2019 (COVID-19) has resulted in catastrophic consequences in many aspects of life; including negative psychological effects. We aimed to assess the mental health status of a group of Saudi population during this pandemic. Also, we aimed to assess the effect of the intensive media coverage of the pandemic news on mental health status. A questionnaire was distributed online to test depression, anxiety, and stress (using the DASS-21 scale) and their relationship to certain variables. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
3
14
0
2
Order By: Relevance
“…The results of a survey conducted in Germany indicated a positive correlation between COVID-19-related media exposure and the severity of nonspecific anxiety and depression [ 18 ]. Similar results were reported in a previous study conducted among the Saudi Arabian general population [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of a survey conducted in Germany indicated a positive correlation between COVID-19-related media exposure and the severity of nonspecific anxiety and depression [ 18 ]. Similar results were reported in a previous study conducted among the Saudi Arabian general population [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study conducted in Wuhan demonstrated that social media exposure was positively associated with anxiety and depression during the COVID-19 outbreak, after controlling for covariates [ 4 ]. These results were supported by those of studies conducted in Germany [ 18 ], Saudi Arabia [ 19 ], and China [ 20 ] indicating that the frequency and duration of media or information exposure may predispose individuals to mental distress. These findings highlight the need to address mental health problems as part of public health policy.…”
Section: Introductionsupporting
confidence: 71%
“…Considering stress and anxiety associated with COVID-19, patients should be advised to limit exposure from multimedia coverage. 149 - 151 Those patients with pre-existing mental conditions should continue treatment and report new or worsening signs and symptoms. 152 - 154…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, widespread media coverage about disasters may extend the boundary of disaster itself and disseminate passive emotions among the population, thereby increasing psychological distress ( 39 ). In fact, the mere exposure of distressing media content is sufficient to provoke negative emotions ( 5 , 6 , 40 , 41 ). During the COVID-19 outbreak, media coverage usually contained numerous stress-inducing contents, such as rumors, misrepresentation, and fear messages, especially media-based graphic images (e.g., diagnosed patients with ventilators), all of which would result in huge psychological stress on the public.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%